PERBANDINGAN PEMILIHAN MODA TRANSPORTASI KENDARAAN ANGKUTAN UMUM DENGAN KENDARAAN PRIBADI : Case Study: City of Sibolga-District of Sibabangun Tapanuli Tengah - Hotriani Malau; Wan Alamsyah; Defry Basrin (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2024)
Transportation is a process of moving people or goods from one place to another. Sibolga City and Central Tapanuli Regency are areas that are always crowded with people from both those areas and from, therefore these places are always crowded with people. Formulation of the problem: Examining the comparison of the choice of public transportation modes with private vehicles from Sibolga City to Sibabangun District. The aim is to find out the comparison of transportation costs for public transport and private vehicles. This research method is quantitative. The results of the research on public transportation are much cheaper than private vehicles with a comparison (0.468 : 0.210). The safety of using private vehicles is much safer than public transportation in comparison (0.309: 0.905). Accessibility level of public transportation is much easier to get access than private vehicles in comparison (0.516 : -0.075). Conclusion: Comparison of the cost of public transportation with private vehicles is equal to (0.468 : 0.231) (46.8% : 23.1%). The cost of using public transport is relatively cheap compared to private vehicles. The safety ratio is (0.309 : 0.905) (30.9% : 90.5%). This means that private vehicles are much safer than public transportation. Comparison of accessibility (ease level) (0.516 : -0.075) (51.6% : -7.5%), meaning that public transportation is much easier to access than private vehicles.